A new computerized and automated grading system for Fresh Fruit Bunches (FFB) in palm oil mill / Ahmed Jaffar … [et al.] - Jaffar, Ahmed; Jaafar, Roseleena; Jamil, Nursuriati; Abdullah, Bulan (Research Management Institute (RMI), 2010)
Malaysia is not the only the world's leading producer and exporter of palm oil butalso the biggest exporter of oils and fats in the world. In keeping its status as world leaderin production of quality palm oil, a lot of research has been done in order to produce palmoil species that can produce higher Oil Extraction Rate (OER). At the moment, thehighest oil extraction rate that can be produced in palm oil fruit is about 25 percent [1]. Oil extraction rate is very important to the palm oil mill because it represents theirproduction performance. Higher oil extraction rate with less amount of Fresh Fruit Bunches (FFB) processed is what palm oil millers aimed to achieve. The oil content inripe palm oil fruits is higher than that of unripe palm oil fruits.